Young Women as Change Agents in Sports and Physical Activities in the Punjab (Southern) Province of Pakistan - Ahmed Laar, Rizwan; Perveen, Shahnaz; Ashraf, Muhamad Azeem (Frontiers in Psychology, 2022)
Women’s empowerment is a concept describing the promotion of women doing things independently and in their own interests, being more conducive to their future and physical and mental development; this includes participation in different outdoor activities, including sports. This qualitative study presents data collected from 18 young female students at sports and physical education universities in Southern Punjab (SP) in Pakistan, selected using a snowball sampling technique. The current study explores their gendered and lived experiences of playing sports and engaging in physical activities in patriarchal systems by emphasizing the concept of women’s empowerment in the context of feminism in sports theory. The findings suggest that the participants faced typical gender stereotypes in their families and communities, which position sports and physical activities as being not feminine. The chances for women to participate in sports and physical activities decrease as they grow up. However, the participants used a range of strategies to advance their interests and academic careers in sports and physical activities by resisting and incorporating dominant discourses of women’s participation in sports and physical activities, which also has implications in the internal and external policy domains at the local and national levels. The participants displayed great resilience and optimism, empowering them to enter the male-dominated domains, and thus we labeled them as change agents.